2011
DOI: 10.1556/oh.2011.29277
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of prostanoids in patients with critical leg ischemia

Abstract: A prosztanoidok (alprostadil, iloprost) azoknál a kritikus végtagischaemiás betegeknél alkalmazhatóak, akiknél a revascularisatiós beavatkozások nem végezhetőek el vagy sikertelenek voltak. Egy Cochrane-elemzés (CD006544) szerint a prosztanoidok hatásossága a fájdalomcsökkenés és fekélygyógyulás terén eltérő. Célitűzés: A vizsgálat célja a prosztanoidok hatásosságának és biztonságosságának értékelése. Módszer: Szisztematikus irodalomkeresés és a randomizált, kontrollált vizsgálatok kevert típusú metaanalízise.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Prostanoids (alprostadil and iloprost) are used for the treatment of patients with critical limb ischemia in whom revascularization procedure was inadequate or proved to be unsuccessful. Brodszky et al reported that alprostadil had favorable effects of rest-pain relief and ulcer healing in critical limb ischemia 19. Besides, a recent study reported that sildenafil (50 mg q 12 hour) was effective in severe peripheral ischemia induced by terlipressin, and that the wound also improved in two weeks 13.…”
Section: Discussionmentioning
confidence: 99%
“…Prostanoids (alprostadil and iloprost) are used for the treatment of patients with critical limb ischemia in whom revascularization procedure was inadequate or proved to be unsuccessful. Brodszky et al reported that alprostadil had favorable effects of rest-pain relief and ulcer healing in critical limb ischemia 19. Besides, a recent study reported that sildenafil (50 mg q 12 hour) was effective in severe peripheral ischemia induced by terlipressin, and that the wound also improved in two weeks 13.…”
Section: Discussionmentioning
confidence: 99%
“…Brodszky et al demonstrated the favourable effect of prostanoids on rest pain relief and ulcer healing in patients affected by critical lower limb ischemia, analysing seven randomised controlled trials including 964 patients. Ruffolo et al analysed data collected from the Cochrane Central Register of Controlled Trials and concluded that further well‐conducted, high‐quality randomised double‐blinded trials should be performed to give definitive data on the long‐term effectiveness and safety of different prostanoids in patients with critical lower limb ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…These include alprostadil (PGE1 analogue) [9], sildenafil [10] and nitrates [11] as reported by various authors. Nevertheless, amputation remains the last resort in limb gangrene.…”
Section: Referencesmentioning
confidence: 99%